(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The presented article analyses the philosophical and cultural features of phraseological units reflecting the concept of happiness of non-related languages. The main focus has been done on the similarity and identity of ideas about happiness reinforced in phraseological units of the English and Uzbek languages based on dictionaries.